Biological Degradation of Soybean Molasses by Modified Anaerobic–Aerobic Baffled Reactor - Mello, Bruna Sampaio de[UNESP]; Rodrigues, Brenda Clara Gomes [UNESP]; Medina, Kelly J. Dussán [UNESP]; Sarti, Arnaldo [UNESP] (Springer Nature, 2022)
Considered a high-volume waste, soybean molasses is the main byproduct of soybean protein concentrate production and is viscous liquid with high concentrations of soluble carbohydrates, proteins, and lipids. The main goal of this study was to evaluate the potential use of soybean molasses as organic matter for biological degradation in a modified anaerobic–aerobic baffled reactor (AABR) for biogas generation. The AABR was designed with four chambers with useful volume of 5 L, spatially separated, being the first three chambers anaerobic, and the fourth chamber aerobic. The reactor was fed with diluted soybean molasses for six operational conditions (0.43 at 3.86 kgCOD/m3 day). The experimental results showed that the anaerobic system efficiency, in terms of CODTotal removal, was particularly good with values between 73 and 95%. Regarding the entire system, the mean value of percentage CODTotal removal was around 88 and 98% which led to the final effluent concentration between 34 and 764 mgO2/L. The results show that AABR has great potential for biological degradation of soybean molasses and production of biogas estimated up to 180,000 m3/year with high concentrations of methane (86%).
Keywords: AABR; Aerobic post-treatment; Agro-industrial waste; Anaerobic digestion; Biogas; Soybean protein concentrate